Controlling radiolysis chemistry on the nanoscale in liquid cell scanning transmission electron microscopy. Issue 33 (17th March 2021) - Lee, Juhan; Nicholls, Daniel; Browning, Nigel D.; Mehdi, B. Layla
Abstract : When high-energy electrons from scanning transmission electron microscope (STEM) are interacting with the liquid, the vast majority of the chemical reactions that are observed are induced by the radiolysis breakdown of the liquid molecules. Abstract : When high-energy electrons from a scanning transmission electron microscope (STEM) are incident on a liquid, the vast majority of the chemical reactions that are observed are induced by the radiolysis breakdown of the liquid molecules. In the study of liquids, the radiolysis products of pure water are well known, and their rate of formation for a given flux of high-energy electrons has been studied intensively over the last few years for uniform TEM illumination. In this paper, we demonstrate that the temporal and spatial distribution of the electron illumination can significantly affect the final density of radiolysis products in water and even change the type of reaction taking place. We simulate the complex array of possible spatial/temporal distributions of electrons that are accessible experimentally by controlling the size, the scan rate and the hopping distance of the electron probe in STEM mode and then compare the results to the uniformly illuminated TEM mode of imaging. By distributing the electron dose both spatially and temporally in the STEM through a randomised "spot-scan" mode of imaging, the diffusion overlap of the radiolysis products can be reduced, and the resulting reactions can be more readily controlled. This control allows the resolution of the images to be separated from the speed of the induced reaction (which is based on beam current alone) and this facet of the experiment will allow a wide range of chemical reactions to be uniquely tailored and observed in all liquid cell STEM experiments.